Work Environment, Organizational Culture, and Leadership Style Shaping Employee Spirit: Budaya Kerja, Budaya Organisasi, dan Gaya Kepemimpinan dalam Membentuk Semangat Karyawan - Rifai, Moh (Indonesian Journal of Law and Economics Review, 2025)
General Background: Employee enthusiasm is a crucial factor in achieving organizational productivity and competitiveness, especially in dynamic industrial environments. Specific Background: CV. Himpunan Abadi in Surabaya faces fluctuating employee motivation, potentially linked to internal conditions such as work environment, organizational culture, and leadership style. Knowledge Gap: Previous studies have rarely examined these three managerial aspects simultaneously within small-scale industrial settings. Aims: This study investigates how work environment, organizational culture, and leadership style collectively relate to employees’ work spirit. Results: Using quantitative analysis with multiple linear regression on 71 respondents, findings revealed that all three variables—work environment, organizational culture, and leadership style—significantly correlate with employees’ work enthusiasm both partially and simultaneously, with leadership style showing the strongest relationship. Novelty: This research integrates behavioral and structural dimensions of management to explain employee morale in a manufacturing-based company context. Implications: The findings provide managerial insight emphasizing leadership development and workplace cultural improvement to foster sustainable employee motivation. Highlights: Leadership style shows the strongest relationship with employee spirit. All three factors significantly correlate both partially and simultaneously. Provides strategic insight for improving workplace morale in small industries. Keywords: Work Environment, Organizational Culture, Leadership Style, Employee Spirit, Human Resource Management